STRATEGI KOMUNIKASI PEMASARAN KOPI JANJI JIWA SAMARINDA MELALUI MEDIA INSTAGRAM UNTUK MENINGKATKAN MINAT BELI KONSUMEN - Farhan Fawwaz; Silviana Purwanti; Fareis Althalets (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Kopi Janji Jiwa builds a commitment to serving quality drinks by increasing marketing through product promotions on social media such as Instagram. Through Instagram Kopi Janji Jiwa creates photo and video content on Instagram media, to attract consumers' attention and be able to send messages that will be conveyed to consumers. The purpose of this study was to determine the marketing communication strategy of Kopi Janji Jiwa Samarinda through Instagram to increase consumer buying interest. The research method uses descriptive qualitative. The key informant is the manager at Kopi Janji Jiwa in Samarinda and the characteristics of the informant are the consumers at Kopi Janji Jiwa in Samarinda. Qualitative data analysis used the Miles and Hubermann techniques. The results of the marketing communication strategy research implemented by Kopi Janji Jiwa Samarinda through Instagram social media are appropriate with several things to support marketing in accordance with the planned objectives. The marketing communication strategy consists of several elements, namely the use of marketing mix theory, namely 4P (product, price, promotion, place), which has been well implemented by Kopi Janji Jiwa Samarinda. The factors that influence the increase in consumer buying interest in the products sold by Kopi Janji Jiwa Samarinda are due to the quality of the products sold by Kopi Janji Jiwa are not careless products but products that are directly selected by people who are professionals in coffee matters and the large selection of products offered so consumers can choose according to their wishes.